Characterisation of caprine islet-related genes and enhancement of islet viability and function by heme oxygenase 1 gene - Vakhshiteh, Faezeh (2013)
Type 1 diabetes is an important health issue since diabetes is related with serious mortality and morbidity worldwide. One promising approach to treat the disease would be transplantation of the islets which are isolated from the donor pancreas into the patient liver via portal vein. However, a high loss of islets after isolation and transplantation is commonly noted which negatively affects the transplant outcomes. Heme oxygenase 1 (HO-1) is a stress protein induced as a protective mechanism in response to a variety of stimuli. Hence, targeted induction of this protein may be considered as a valuable therapeutic strategy for the protection against inflammatory processes and oxidative tissue damages. The first aim of the current study was to sequence goat HO-1 mRNA. Once the HO-1 mRNA was sequenced, the vector encoding goat HO-1 was constructed and later transfected into the islets. Insulin is the most important hormone of the pancreas, hence, the second objective of the study was aimed to clone and sequence a cDNA encoding an insulin protein in the caprine species. The study was also designed to investigate the transient response of the caprine islets for insulin secretion as well as insulin gene expression after glucose exposure in short period (1 h). The current study also aimed to determine and differentiate the insulin secretion and cell death in association with the size of caprine islets. In this regard, caprine islets were isolated by collagenase digestion and purified by discontinuous Ficoll density gradient centrifugation. Isolated caprine islets were transfected with expression vector containing goat HO-1 gene and cultured for 5 days. The efficacy of GFP transfer to islets was quantified by flow cytometry. Western blots were applied to verify the expression of HO-1 protein. Glucose stimulated insulin release was measured using insulin ELISA assays. Meanwhile, the islet viability was evaluated by the Cell-Titer blue viability assay. Goat HO-1 cDNA was encoding a 288-amino acid protein with a predicted molecular mass of 32.75 kD. The cDNA of goat insulin was successfully amplified using a pair of specifically designed primers. Pairwise comparison showed that goat insulin protein (partially sequenced) was highly similar to insulin protein deposited in public databases, especially cattle preproinsulin with 93% homology. Goat insulin was also similar to human preproinsulin with 72% identity. It was shown that stimulation of insulinproducing cells with high glucose concentrations for only an hour resulted in transient elevation of insulin gene transcription, as verified by measurements of insulin mRNA levels. It was found that isolated caprine islets of large diameter could not be maintained efficiently in culture compared to small islets. After 48 h of culture, small islets showed 2.33% necrosis while a large proportion of necrotic cells was detected in cultured large islets (29.5%). The small and large islets showed an apoptotic death pattern of 5.21 and 7.34%, respectively. Small islets were 92.46% viable, while the viability of the large islets was 63.16%. At 48 h post isolation, under basal conditions, the small islets release 1.39 ± 0.2 ng/IE insulin. With a high glucose concentration, the secreted insulin increased to 2.95 ± 0.33 ng/IE. For the large islet equivalencies, the insulin release under basal conditions and with a high glucose concentration were 0.489 ± 0.2 and 1.01 ± 0.26 ng/IE, respectively. Based on the results, after 2 days of culture, the insulin release with low and high glucose stimulation in large and small islets decreased significantly which clearly indicated that the islet function decreased gradually over time in in vitro culture. In the present study, to ensure the lipidmediated transfection efficiency into the islets, optimization was first done using a reporter protein (Green Fluorescent Protein, GFP). After optimization, transfection and expression of the goat native HO-1 protein in the islet were investigated to determine islet functional outcome after 5 days of cultures in vitro. The insulin stimulation index (SI) in control islets (non-transfected) was 2.02 ± 0.026 while the SI in GFP and HO-1 transfected islets was 1.97 ± 0.026 and 2.07 ± 0.030, respectively. In conclusion, caprine islets could be suitable alternatives for human transplantation with regard to high similarity of the insulin gene to that of pig and human. The study showed that small islets were superior large islets in viability and insulin release under low and high glucose conditions in vitro culture 48 h postisolation. Therefore, protection from core cell death in transplanted islets may improve the success of transplantation by reducing the routine non-functionality of the grafted islets. Transfection of caprine islets with native HO-1 can improve viability and function of the cultured islets which might subsequently increase success of islet transplantation.